Medioevo restaurato: la chiesa di Sant'Eligio Maggiore a Napoli - De Feo (UrbsHistoriaeImago, 2023)
The church of Sant'Eligio Maggiore (or al Mercato) is the first Angevin religious building of Naples. Its current configuration is the result of numerous stratifications which, have completely rewritten several times on the remains of the structures of the past, making today difficult, if not impossible, the reading of some construction phases of the architectural palimpsest. The main objective of the research was the construction and experimentation of a methodology that would facilitate the understanding of Neapolitan medieval buildings. With a multidisciplinary approach, comparing the information coming from the digital survey, from the archival, iconographic and bibliographic data, it was possible to clarify some aspects relating to the late medieval construction phases, the modern age renovations and the contemporary restorations of the church, with significant advances in knowledge.